Application of questionnaires in the assessment of clinical severity of chronic rhinosinusitis - Stupar, Marija; Špreng, Djordje; Perić, Aleksandar (Vojnosanitetski pregled, 2021)
Background/Aim. Diagnosis of chronic rhinosinusitis (CRS) is based on clinical symptoms, and confirmed with endoscopic findings and computed tomography (CT) scans of paranasal sinuses. However, the results of numerous studies have shown that the symptoms that patients report are not in correlation with the degree of the disease spread obtained by radiological findings. The aim of our study was to examine is there a correlation between the degree of symptoms intensity of the non-polypous and polypous form of CRS and the degree of the disease spread, obtained on the basis of radiological diagnostics. Methods. A total of 60 patients, of which 30 patients with CRS without nasal polyps (CRSsNP) and 30 with CRS with nasal polyps (CRSwNP), were included in this cross-sectional study. Symptoms were evaluated using two questionnaires: Sino-Nasal Outcome Test 22 (SNOT-22) and Visual Analogue Score (VAS). The Lund Mackay CT score was used as a radiological parameter of the disease expansion. In addition, each of the subjects was examined for sensitivity to standard inhalation allergens. Results. In patients with CRSsNP, there were statistically significant positive correlations between the Lund Mackay CT score and the SNOT-22 score (r = 0.578, p = 0.001) and between the Lund Mackay CT score and the VAS (r = 0.408, p = 0.025). We found no correlation between the both questionnaire scores and the Lund Mackay score in CRSwNP patients. In patients with CRSwNP, a statistically significant difference was found in the values of SNOT-22 between patients with and without sensitivity to inhalation allergens, with higher values of the score in patients with allergy (p = 0.039). Conclusion. There is a positive correlation between the severity of the symptoms and the radiological findings only in patients with CRSsNP, which suggests that application of these questionnaires would be possible only in the case of this clinical entity.
Keywords: rhinitis; sinusitis; chornic disease; surveys and questionnaires; signs and symptoms; diagnosis